2015
DOI: 10.1016/j.rbr.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre o Disease Activity Score‐28 e o Juvenile Arthritis Disease Activity Score na artrite idiopática juvenil

Abstract: The conversion of scores of DAS-28 and JADAS 71, 27 and 10 for this mathematical model would allow equivalent application of both in adolescents with arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although previous studies found good correlations between DAS28 and JADAS in children with JIA, 8 this is the first to include the adult population and highlight a discrepancy in thresholds for high-disease activity between DAS28 and JADAS.…”
mentioning
confidence: 53%
“…Although previous studies found good correlations between DAS28 and JADAS in children with JIA, 8 this is the first to include the adult population and highlight a discrepancy in thresholds for high-disease activity between DAS28 and JADAS.…”
mentioning
confidence: 53%